Penguatan Budaya Penegakan Hukum Pada Penerapan ISO 37001 Untuk Meningkatkan Pelayanan Publik - Yustisia Andang Ardhiantoro (Program Studi Ilmu Pemerintahan Universitas Muhammadiyah Buton, 2022)
Bribery in public service has been a worrying issue in Indonesia. The government has issued several regulations which is President Instruction Number 10/2016 regarding Preventive Action and Corruption Eradication as the one. The implementation of such regulation is the prevailing of Anti-Bribery Management System ISO 37001:2016 to control bribery practice. However, the fact shows that the number of bribery actions still became the most committed crimes in every year. bribery in public service has been a strong culture so no matter how well the regulation and regulatory policy is still difficult to overcome such issues. Therefore, the new culture is required to against the bribery existing culture through improving the Anti-Bribery Management System ISO 37001:2016 by strengthening enforcement law culture. Using the qualitative method with a descriptive approach, the Author tries to combine those crucial aspects between the implementation of the Anti-Bribery Management System ISO 37001:2016 and strengthening enforcement law culture which hopefully the regulation can be implemented optimally for improving public service.